Design the wave attenuation property of nacreous composites. (October 2020) - Liu, Junjie; Hai, Xusheng; Wei, Xiaoding
Abstract: Wave filtering or attenuation is largely demanded in many fields, such as vibration isolation and acoustic damping. Here, we investigate the wave propagation in nacre-like staggered composites based on the dynamic shear-lag model. Our analyses explicitly establish the connections between band structures and the constituents' properties as well as geometries of building-blocks. For composites consist of purely linear-elastic constituents, their high-frequency bandgaps can be designed effectively by adjusting the dimensionless overlap length of unit cells. In comparison, filtering low-frequency waves (with a dimensionless frequency less than (1) is challenging in linear-elastic staggered composites. More importantly, our analyses suggest that when the matrix viscosity presents, there are no more passbands in the composites. The wave attenuation can be optimized by synergetic designs of the constituents' properties and building block morphologies.